(untitled) (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
Author Dr. Nagalla Bhargav Kumar Assistant Professor, Dept. of Pharmacy Practice, Sultan-ul-Uloom College of Pharmacy, Hyderabad, Telangana India Abstract Standardized patient assessment comprises of data collection through validated tools and systematic documentation methods. Electronic health record systems enable structured documentation of patient data, interventions, and outcomes. Care plan development follows evidence-based algorithms incorporating patient-specific factors, comorbidities, and treatment goals. Monitoring strategies utilize validated indicators to track therapeutic response, adverse effects, and clinical outcomes. Outcome evaluation methods measure treatment effectiveness through standardized metrics, including clinical parameters, functional status, and quality of life measures. Implementation of systematic care processes requires coordinated interprofessional collaboration and regular protocol updates based on outcome data analysis. Keywords: Patient assessment, Care planning, Clinical monitoring, Outcome measurement, Documentation systems VIEW PDF